2021
DOI: 10.1002/cam4.3890
|View full text |Cite
|
Sign up to set email alerts
|

Normal tissue adjacent to tumor expression profile analysis developed and validated a prognostic model based on Hippo‐related genes in hepatocellular carcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…A recent study on histologically normal breast epithelium by Graham K et al suggested that the microenvironment surrounding the tumor is essential for understanding recurrence [ 33 ]. In line with this phenomenon, the NAT molecular profile is reported to show the prognostic significance for recurrence in patients with different cancers including CRC [ 2 , 3 , 4 ], HCC [ 5 ], prostate [ 6 ], oral carcinoma [ 7 ], breast cancer [ 8 ] and head and neck cancer [ 9 ]. Further investigation on CBX8, as well as other dysregulated NAT molecular markers, for prognosis of CRC patients, warrants evaluation for their clinical use.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A recent study on histologically normal breast epithelium by Graham K et al suggested that the microenvironment surrounding the tumor is essential for understanding recurrence [ 33 ]. In line with this phenomenon, the NAT molecular profile is reported to show the prognostic significance for recurrence in patients with different cancers including CRC [ 2 , 3 , 4 ], HCC [ 5 ], prostate [ 6 ], oral carcinoma [ 7 ], breast cancer [ 8 ] and head and neck cancer [ 9 ]. Further investigation on CBX8, as well as other dysregulated NAT molecular markers, for prognosis of CRC patients, warrants evaluation for their clinical use.…”
Section: Discussionmentioning
confidence: 90%
“…The 5-year survival rate remains below 65% in developed countries and under 50% in developing countries [ 1 ], mainly due to recurrence and metastasis. Recent studies demonstrated that the molecular profile of normal tissue adjacent to the tumor (NAT) is prognostic for recurrence in patients with different cancers including CRC [ 2 , 3 , 4 ], HCC [ 5 ], prostate [ 6 ], oral carcinoma [ 7 ], breast cancer [ 8 ] and head and neck cancer [ 9 ]. We believe a better understanding of the molecular profile in NAT is crucial for identifying molecular biomarkers for predicting the prognosis of CRC patients and therapeutic targets to combat recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…However, we suggest MINK1 as a novel candidate gene for autism, congenital cataract, epilepsy and osteoporosis. Although we report the first patient with disruption of MINK1 , the gene has already been implicated in a variety of disorders based on cohort studies in humans, in silico models and work on model organisms, including congenital heart disease in humans [ 20 ] and skeletal and neuronal phenotypes in mice [ 21 , 22 ], as well as cancer [ 23 , 24 ], platelet formation [ 25 ], Alzheimer disease [ 26 , 27 ] and arthritis [ 28 ]. As such, it appears that MINK1 is part of a diverse set of biological processes, which is expected as MINK1 is highly expressed in a variety of tissues ( Figure 2 B) and interacts with a diversity of proteins ( Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…As far as is known, this is the rst study to emphasize lncRNAs in tumor-adjacent tissues. It has been reported that signals detected from tumor-adjacent tissues could build a superior prognosis model and better predict cancer recurrence (22,23) because 40% of these tissues already exhibited aberrant genomic features (24). We hope that analyzing lncRNAs from these tissues can 1) explore the tumor microenvironment where signals from the tumor and surrounding adipose can be better captured; 2) identify the secretions present in tumor-adjacent cells that could be detected in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%